Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1093/rheumatology/kead075
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography for malignancy screening in patients with rheumatoid arthritis before initiation of disease modifying antirheumatic drug

Abstract: Objectives This study aimed to clarify the usefulness of screening for malignancies using computed tomography (CT) before the initiation of biologics and targeted synthetic disease-modifying antirheumatic drugs (b/tsDMARDs) in patients with active rheumatoid arthritis (RA). Methods We examined 2,192 patients with RA who underwent plain CT scans prior to the initiation of b/tsDMARDs. The sensitivity for detecting malignancy wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The United States Preventive Services Task Force recommends yearly screening tests by chest CT for those in the 50–80 age groups with 20‐pack‐year smoking histories and those who are currently smoking or within 15 years of quitting 25 . Miyata et al 26 . performed CT screening on 2192 patients with RA who required the introduction of biological or targeted synthetic DMARDs and reported that 15 had lung cancer.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The United States Preventive Services Task Force recommends yearly screening tests by chest CT for those in the 50–80 age groups with 20‐pack‐year smoking histories and those who are currently smoking or within 15 years of quitting 25 . Miyata et al 26 . performed CT screening on 2192 patients with RA who required the introduction of biological or targeted synthetic DMARDs and reported that 15 had lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…performed CT screening on 2192 patients with RA who required the introduction of biological or targeted synthetic DMARDs and reported that 15 had lung cancer. Furthermore, 80% of patients with RA and lung cancer had stage I disease, and curative resection was performed in all cases, indicating that CT screening was useful for the early detection of lung cancer, even in patients with RA with high disease activity 26 . Considering that the incidence of lung cancer in patients with RA is higher than that in the general population, annual chest CT screening is mandatory for those with a history of smoking.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients who met the ACR/EULAR 2010 RA classification criteria and did not respond to phase I therapy were referred to UOEH for further evaluation of eligibility for b/tsDMARDs. This comprehensive evaluation included assessment of contraindications and consideration of comorbidities, such as screening for infectious diseases and malignancies [ 23 ]. Subsequently, the administration of the b/tsDMARDs was decided by the patients and the treating physician under the guidance of recommendations/guidelines [ 1 , 2 , 24 ].…”
Section: Methodsmentioning
confidence: 99%